A Unique High‐Output Cardiac Hypertrophy Phenotype Arising From Low Systemic Vascular Resistance in Cantu Syndrome - Singh, Gautam K.; McClenaghan, Conor; Aggarwal, Manish; Gu, Hongjie; Remedi, Maria S.; Grange, Dorothy K.; Nichols, Colin G. (Journal of the American Heart Association, 2022)
Background Cardiomegaly caused by left ventricular hypertrophy is a risk factor for development of congestive heart failure, classically associated with decreased systolic and/or diastolic ventricular function. Less attention has been given to the phenotype of left ventricular hypertrophy with enhanced ventricular function and increased cardiac output, which is potentially associated with high-output heart failure. Lack of recognition may pose diagnostic ambiguity and management complexities. Methods and Results We sought to systematically characterize high-output cardiac hypertrophy in subjects with Cantu syndrome (CS), caused by gain-of-function variants in , which encodes cardiovascular K (ATP-sensitive potassium) channel subunits. We studied the cardiovascular phenotype longitudinally in 31 subjects with CS with confirmed variants (median [interquartile range] age 8 years [3-32 years], body mass index 19.9 [16.5-22.9], 16 male subjects). Subjects with CS presented with significant left ventricular hypertrophy (left ventricular mass index 86.7 [57.7-103.0] g/m in CS, n=30; 26.6 [24.1-32.8] g/m in controls, n=17; <0.0001) and low blood pressure (systolic 94.5 [90-103] mm Hg in CS, n=17; 109 [98-115] mm Hg in controls, n=17; =0.0301; diastolic 60 [56-66] mm Hg in CS, n=17; 69 [65-72] mm Hg in control, n=17; =0.0063). Most (21/31) subjects with CS exhibited eccentric hypertrophy with normal left ventricular wall thickness. Congestive heart failure symptoms were evident in 4 of the 5 subjects with CS aged >40 years on long-term follow-up. Conclusions The data define the natural history of high-output cardiac hypertrophy resulting from decreased systemic vascular resistance in subjects with CS, a defining population for long-term consequences of high-output hypertrophy caused by low systemic vascular resistance, and the potential for progression to high-output heart failure.